Effect of low concentrations of indoor toluene on cognitive performance: EEG-based evidence. (October 2022) - Wang, Zukun; Liu, Junjie; Wang, Jiajing; Guo, Dandan; Pei, Jingjing; Zhao, Lei; Zhang, Xin; Liu, Jie; Li, Yuying; Deng, Meili; Cui, Mingrui; Yang, Yuan; et al.
Abstract: The influence of volatile organic compounds (VOCs) on cognitive performance has been widely recognized but is still imperfectly understood. This article hypothesized that the influence of low concentrations of VOCs on cognitive function would occur without triggering subjective awareness. Toluene is a representative VOC commonly found in Chinese dwellings. A within-subject experiment was conducted to compare working memory performance and electroencephalographic patterns of participants exposed to toluene at 70 ppb (Tol group), a WHO-recommended toluene exposure limit, and at 0 ppb (Ctrl group) in a controlled environment chamber. Results demonstrated that toluene exposure at the ppb level could change neural arousal patterns during working memory tasks in healthy subjects, although there was no significant difference in task performance. Compared with the Ctrl group, power spectral density analysis showed that the alpha and theta bands in the frontal region of the Tol group increased considerably in both the encoding and maintenance periods (P < 0.01 for theta, P < 0.05 for alpha). The direct transfer function indicated that the functional connectivity of the frontal network in the theta band, gamma band, and alpha band significantly decreased (P < 0.01 for all bands above). In contrast, the functional connectivity of the frontoparietal network increased under toluene exposure in the theta and alpha bands during the maintenance period (P < 0.01 for both bands). This study proved the feasibility of a potential evaluation method using neurobehavioral tests with electroencephalography (EEG) analysis. Graphical abstract: Image 1 Highlights: A 70-ppb toluene exposure can change working memory pattern in healthy subjects. The effect of toluene exposure appeared mainly in the alpha and theta bands. Toluene changed the functional connectivity of the frontoparietal networks. A potential indoor air quality evaluation system with EEG was proposed.